Global burden of atrial fibrillation/atrial flutter and its attributable risk factors in adolescents and young adults, 1990–2021: insights from the global burden of disease study - Xueyao Zhang; Yanli Chen; Wenyu Hu; Saien Lu; Haijie Yu; Yingxian Sun (Annals of Medicine)
Objective The aim of this study is to evaluate the global burden trends of atrial fibrillation/flutter with attributable risk factors among adolescents and young adults from 1990 to 2021, particularly in the context of the increasing prevalence of cardiovascular diseases in younger populations.Materials and methods Disease burden data for atrial fibrillation/atrial flutter were sourced from the 2021 Global Burden of Disease Study. The primary metrics were incidence, disability-adjusted life years, and mortality. Population attributable fractions were used to calculate the percentage contribution of the major underlying risk factors to the disease burden.Results From 1990 to 2021, the global burden of atrial fibrillation/atrial flutter among the studied population increased by 57.26% in incidence, 71.32% in mortality, and 62.34% in disability-adjusted life years. The rate increases were 15.87%, 26.22%, and 19.61%, respectively. The burden of atrial fibrillation/atrial flutter in 2021 and its temporal trends varied significantly according to sex, sociodemographic index quintiles, and geographic location. In 2021, the burden was the highest in the middle-sociodemographic-index regions. Sex differences were found in all potential risk factors of atrial fibrillation/atrial flutter–related mortality and disability-adjusted life year rates. The top three potential risk factors in men were high systolic blood pressure, tobacco exposure, and high alcohol use, and in women, high systolic blood pressure, high body mass index, and tobacco exposure.Conclusion An imbalance in disease burden across different regions exists. The rapidly increasing disease burden warrants attention, and prevention and treatment strategies should be adjusted to prevent further increase.